One last stand - Warren, Susan May, 1966- (Warren, Susan May, 1966- Sky King Ranch, 2024)
"When Air One Rescue pilot London Brooks finds herself falsely accused, her reputation tarnished, and her life in danger, she has no choice but to plunge back into the treacherous world of espionage she left behind. Shep Watson already saved London's life once-and he'll do everything in his power to bring her back home"--